Kyrgyz Republic Economic Update No. 1, Spring 2015 : Adjusting to a Challenging Regional Economic Environment - World Bank (World Bank, Washington, DC, 2021)
Growth in the Kyrgyz Republic slowed significantly in 2014, reflecting the deteriorating external environment and supply-side constraints. Economic growth fell to 3.6 percent in 2014 from 10.9 percent in the previous year, partly because exports to Russia and other neighboring countries plunged. Re-export businesses were affected as the Eurasian Economic Union (EEU) began to exercise stricter border control on goods imported from third countries. On the supply side, lower production at the Kumtor gold mine and a poor harvest due to adverse weather also depressed growth. The fall of the Russian ruble and the Kazakh tenge led to a significant depreciation of the Kyrgyz sum, which together with increases in energy tariffs drove inflation up from 4 percent in 2013 to 10.5 percent in December 2014. Although export growth was negative (–6.4 percent), imports declined even more (–7.2 percent), which, together with lower income outflows, helped to reduce the current account deficit from 15 percent in 2013 to 13.7 percent of GDP. The current account deficit was financed by borrowing and foreign direct investment (FDI). On the fiscal side, slower growth affected tax revenues, which were essentially flat at 25.3 percent of GDP but non-tax revenues went up by over a percentage point of GDP, to 6.7; together with grants, that brought total revenues to just under 35 percent of GDP. Meanwhile, a significant expansion of public investment spending brought the deficit to an estimated 4.1 percent of GDP in 2014, up from 3.9 percent in 2013, despite less spending on recurrent outlays. Higher spending and the depreciation of the sum translated into a significant increase in public debt, from 46.1 percent of GDP in 2013 to 53 percent for 2014. Job creation was stagnant. Poverty remained high: the most recent (2013) national estimates are absolute poverty 37.0 percent and extreme poverty 2.8 percent.